res2+, a new member of the cdc10+/SWI4 family, controls the 'start' of mitotic and meiotic cycles in fission yeast. - Miyamoto, M (1994)
In the fission yeast Schizosaccharomyces pombe, the cdc10+ and res1+ genes play a crucial role in the start of mitotic and meiotic cycles. They encode structurally related transcriptional complex proteins and regulate some S phase-specific genes. Here we report the identification of a new member of this family named as res2+. res2+ has been isolated as a multicopy suppressor of a res1- null mutant and specifies a 73 kDa protein, which has two copies of the Swi/ankyrin motif and shares the highest sequence and structure similarity with the Res1 protein. res2+ is largely redundant in function with res1+ and is required for the initiation of mitotic and premeiotic DNA synthesis, but has an additional role in meiotic division. Unlike res1+, res2+ is highly induced during conjugation and strongly depends on cdc10+ for its activity. We conclude that the fission yeast contains two functionally overlapping parallel 'start' systems, Res1-Cdc10 and Res2-Cdc10, the former of which plays a major role in mitotic cycle whereas the latter in meiotic cycle.